A brief note on the attempts of the secularizing powers in the domains of education and administration during the colonial era in the Malay World - Ozay, Mehmet (Ilmi Etudler Dernegi, 2012)
In this article, the phenomenon of secularization will be examined briefly in the context of the colonization process in British Malaya and the Dutch East Indies (Indonesia). Given the relationship between secularization and modernization, it is argued that secularization was brought to and implemented in Southeast Asia, whose population is nearly half Muslim, as a result of different historical processes. In this context, as dealt with in detail in subsequent pages, while the related Western powers functioned as secularizing powers, they did not do so in a revolutionary way, and instead adopted an evolutionary method. As such, it may be remarked that the process extended over a longer period of time and with different layers. It should be underlined here that the fact that modernization occured simultaneously with the adoption of secularization in Europe is also reflected in other geographies, particularly in Southeast Asia due to the colonization process. The Western colonial elements not only constituted economic power, but also attained a crucial role through political and, more particularly educational institutions which led to the secularization of Malay communities, either implicitly or explicitly. Nevertheless, by taking this process into consideration, although it might not have been realized in a revolutionary manner can be argued that the secularization was imposed over a long process while encompassing various layers of Malay societies.